RESEARCH AND DEVELOPMENT OF NANO-STRUCTURED CAPACITOR MATERIAL BY USING ?-IRRADIATION - Yunasfi, -; Mustofa, Salim (Teknologi Indonesia, 2014)
Research and development on the usage of g-irradiation against nano-structured graphite which is suitable for capacitor material has been carried out. The nano-structured graphite in the form of pellet was irradiated by g-ray with variation of dose, from 100 kGy up to 600 kGy. In this research, the analysis of phase changes, the change of electrical resistivity (r), dielectric constant (er) and dielectric loss (tan d), have been carried out to the nano-structured graphite after irradiated by g-ray. The results of XRD showed that g-radiation could decline the peak intensity. The peak intensity decreased with the addition of radiation dose. Electrical resistivity values (r) also fell as an impact of g-radiation, where the decline continues with increasing radiation dose, while the value of the dielectric constant (er) has increased by g-radiation and increased steadily with the increasing of radiation dose. For the case of tan d t?? he tendency was decreased by the g-radiation and this decline continued with the increasing radiation dose. This fact suggests that there has been an interaction between g-radiation with graphite particles which can cause the impactof changes in the structure of graphite. More impact of changes in the structure of graphite is assumed that greater of energy can be stored, thus diminishes the r value and tan d, while the value of er increases.